PENGARUH LAMA FERMENTASI DAN DOSIS SERBUK GERGAJI KAYU JATI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium cepa L.) Var. BIRU LANCOR - Retno Tri Purnamasari; A. Zainul Arifin; Fajar Hidayanto; Ilmiyah Ilmiyah (BUANA SAINS, 2023)
This study aims to determine whether there is a significant difference in the composting time of teak sawdust and the dose of teak sawdust on the growth and yield of shallots of the lancor blue variety. This research was conducted in Tidu Village, Pohjentrek District, Pasuruan Regency. This study used a factorial randomized block design (RBD) method consisting of two factors repeated three times. The first factor is the composting time (L) with L1: 4 weeks, L2: 6 weeks, and L3: 8 weeks. The second factor was the dose of teak sawdust (M) with doses of M1: 5 tonnes ha-1 , M2: 10 tonnes ha-1 , and M3: 15 tonnes ha1 . Overall there were nine treatment combinations. The results showed that composting time of 8 weeks and sawdust dosage of 15 tonnes ha1 resulted in a dry weight of wind on shallot bulbs of 10.74 tonnes ha-1